THE LINGUISTIC EVOLUTION OF INDO-EUROPEAN RIVER NAMES - Sevara Muradova Zoir qizi (Bright Mind Publishing, 2025)
This article explores the etymology and linguistic development of river names (hydronyms) from Ancient Greek ποταμός (potamós) through Celtic and Old English contexts across Northern England and Continental Europe. Using Proto-Indo-European roots such as kweth₂- (‘foam, seethe’) and *is-/eis- (‘to move swiftly’), the study traces how primary lexical elements evolved into complex hydronyms reflecting physical characteristics and cultural interactions.
Keywords: Hydronyms, Proto-Indo-European roots, river names,etymology Celtic toponymy, phonological chang,lenition, ā-mutation (ā-affection).